Qitianniu zhihaoi gen. et sp. nov.: The first cerambycid beetle found in Cretaceous Burmese amber (Coleoptera: Chrysomeloidea). (July 2017) - Lin, Mei-Ying; Bai, Ming
Abstract: A new cerambycid beetle ( Qitianniu zhihaoi gen. et. sp. nov.) is described on the basis of a single specimen embedded in Cretaceous Burmese amber (ca. 99 Ma). Unusual characteristics are hairy antennae and large lateral eyes, a pronotum with lateral margin, and sinuate protibiae. Based on a phylogenetic analysis, the systematic position of Qitianniu is still uncertain and we provisionally place it as Cerambycidae incertae sedis .